Balance of Payments Statistics Yearbook, 2007. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2007)
The BOPS Yearbook, usually published in December, contains balance of payments statistics for most of the world, compiled in accordance with the IMF's Balance of Payments Manual. Part 1 includes aggregate as well as detailed information in the form of analytical and standard component presentations for countries. Part 2 provides tables of data, featuring area and world totals of balance of payments components and aggregates. Part 3 presents descriptions of methodologies, compilation practices, and data sources used by individual member countries in compiling their balance of payments and international investment position statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: General Financial Markets; Investment Decisions; Portfolio Choice